Internationalization of Ethiopian Higher Education Institutions: Manifestations of a Nascent System. (November 2018) - Tamrat, Wondwosen; Teferra, Damtew
The changing landscape of higher education over the past few decades has increasingly brought internationalization to the fore as one major manifestation of the educational systems of both developed and developing countries alike. As part of this global trend, the Ethiopian higher education sector has, in the past decade, begun to exhibit some of the emerging trends of internationalization despite the paucity of data that portray the phenomenon in an organized manner. This study was conducted to address the prevailing deficiencies with particular focus on identifying the dominant manifestations of internationalization in Ethiopia's public and private higher education institutions. Data were drawn from nine public and six private institutions using questionnaire and focus group discussion. The major findings of the study revealed that institutions consider internationalization as an important activity for the purposes of promoting teaching and resource mobilization, international research projects, and academic quality and standards. However, in most of the surveyed universities, internationalization was found to be more of an ad hoc and reactive process than a systematically administered proactive undertaking. On the basis of the findings that portray the features of a nascent system, the need for cohesive policies, strategic directions, and operational efficiencies both at national and institutional levels has been projected.